Modern Principles of the Effect of Heavy Metal Salt on the Body (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article provides a statistical analysis of modern principles of the effects of heavy metal salts on the human body. For this purpose, foreign and domestic scientific articles and scientific research results were analyzed.